Research on Factors Influencing Knowledge Contribution in Online Q&A Communities: Based on an Empirical Study of QCA on Zhihu - Wenzhu Li; Juan Du; Xin Feng; Jiangfei Chen (SAGE Open)
An important reason for the slowdown of online Q&A (Question and Answer) communities is that the number of users with knowledge input behavior is relatively small and the intensity of input behavior is decreasing, which is precisely the key to the sustainable development of communities. Therefore, it is of great significance to explore the factors affecting knowledge contribution behavior to maintain the sustainable development of the community. Based on the social exchange theory from the perspective of configuration, the theoretical model of the factors influencing knowledge contribution behavior is constructed by sorting out nine dimensions of variables from users’ self-improvement and social identity, writing a distributed crawler program to capture a total of 5,000 sample data from Zhihu community, using fuzzy set qualitative comparative analysis for empirical research. We found that users’ knowledge contribution behavior is influenced by multiple prefactors, there may be three different types of constitutive paths that influence users’ knowledge contribution behavior: self-improvement, social identity, and both. At the same time, users’ self-improvement and social identity play a linkage role and jointly influence knowledge contribution behaviors. From the perspective of configuration, the platform can find multiple influencing factors in various ways, so as to enhance the enthusiasm of users for knowledge contribution and promote the sustainable development of the online Q & A community. In addition, this paper further deepen the study of the factors influencing knowledge contribution behavior and develop new research perspectives for the study.